Exrtaction of sericin from degumming process of silk fibres and its application on nonwoven fabrics - Fatahian, Reyhaneh; Noori, Mehdi; Khajavi, Ramin (International Journal of Advanced Chemistry, 2017)
Silk sericin is a family of water-soluble proteins extracted from the silkworm cocoon. Studies have been attempted to recycle the sericin waste sericulture to develop value-added products in biomedical, pharmaceutical, cosmetic and food industries. Thus, increased production of sericin-containing wastewater from sericulture is predicted soon.Â  In this study, some of the separation methods of sericin from silk waste water solution also extracted sericin characteristics have been investigated by FTIR. This study has determined antibacterial action of sericin in E. coli and Micrococcus luteus samples and illustrated sericin capacity as an antibacterial factor by confirming sericin on bacterial growth. Results of this study indicated discretion possibility of sericin from silk wastewater. Extracted sericin value depends on temperature and time. Characteristics of nonwoven textile coated by sericin had represented increasing of tensile and bending length and also showed that sericin with high concentration had preventive capacity of Micrococcus luteus bacterial on nonwoven textile.